2018
DOI: 10.3389/fpsyg.2018.02048
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Similarity to Known Second Language Words Impacts Learning of New Meanings

Abstract: Second language (L2) learners need to continually learn new L2 words as well as additional meanings of previously learned L2 words. The present study investigated the influence of semantic similarity on the growth curve of learning of artificially paired new meanings of previously known L2 words in Chinese–English bilinguals. The results of a translation recognition task showed that related meanings are learned faster and more accurately than unrelated meanings. The advantage of learning related new meaning pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…In recent years, some researchers have realized the importance of L2 ambiguous word learning and conducted meaningful studies (Bracken et al, 2017;Lu et al, 2017;Zhang et al, 2018Zhang et al, , 2020. For example, in the study of Lu et al (2017), to simulate the process of L2 ambiguous word learning, the authors paired each English pseudoword with one meaning or two unrelated meanings and asked participants who were native Chinese speakers to learn these pairs in sequence.…”
Section: Studies On L2 Ambiguous Word Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, some researchers have realized the importance of L2 ambiguous word learning and conducted meaningful studies (Bracken et al, 2017;Lu et al, 2017;Zhang et al, 2018Zhang et al, , 2020. For example, in the study of Lu et al (2017), to simulate the process of L2 ambiguous word learning, the authors paired each English pseudoword with one meaning or two unrelated meanings and asked participants who were native Chinese speakers to learn these pairs in sequence.…”
Section: Studies On L2 Ambiguous Word Learningmentioning
confidence: 99%
“…2.3.1 | Learning stimuli in the word learning task One hundred and twenty English-Chinese word pairs were taken from Zhang et al (2018), in which the English words were familiar and highly recognizable and had one single dominant translation, based on the translation norms of Wen and van Heuven (2017). The 120 English-Chinese word pairs were equally divided into 3 different learning types.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…In Zhang et al (2018) study, Chinese learners of English were asked to learn familiar English words which were paired with a new related or unrelated Chinese meaning over 3 consecutive days. A test (translation recognition) was performed immediately after the learning phase each day.…”
Section: Previous Studies On Ambiguous Word Learningmentioning
confidence: 99%
“…Although Zhang et al (2018) has found that the L2 known meaning affects the late-learned meaning, the question how those multiple meanings interact with each other during L2 ambiguous word learning remains unclear, since Zhang et al (2018) only explored the effect of a previously learned meaning on a late-learned meaning. Moreover, the learning and retrieving phases cannot be easily separated in their experimental design.…”
Section: Previous Studies On Ambiguous Word Learningmentioning
confidence: 99%